Pertanggungjawaban Platform Alami Sharia Terhadap Lender Atas Gagal Bayar Borrower Perspektif DSN-MUI NO. 117/DSN-MUI/II/2018 - Jundi Zakiyah; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the form of liability of PT. Alami Fintek Sharia for borrower defaults to lenders. The focus of this study is the form of liability of the Alami Sharia platform, as the operator of Peer-to-Peer (P2P) Lending, toward lenders regarding borrower defaults, as well as whether such liability complies with the provisions of DSN-MUI Fatwa No. 117/DSN-MUI/II/2018 on Information Technology-Based Financing Services Based on Sharia Principles. This study is motivated by the risk of borrower default in Sharia fintech services, such as the Alami Sharia platform, which raises questions regarding the scope of the platform liability toward lender an issue that requires analysis in light of the provisions of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This study employs an empirical legal research design, utilizing both a statutory approach and a conceptual approach. Data were collected through interviews and a literature review, and were subsequently processed and analyzed using qualitative methods. The results of the study indicate that the Alami Sharia platform asserts that the risk of default by the borrower is a risk inherent to the lender as the shahibul maal. The platform is not directly liable for losses arising from a borrower default, provided there is no element of negligence (taqsir), fault (ta’addi), or violation of the principle of due diligence in the selection and disbursement of financing; clauses transferring liability to the lender violate the Consumer Protection Law. However, efforts to recover the lender’s losses have not yet been effective due to the predominantly administrative nature of law enforcement. Therefore, enhanced legal accountability and the development of better protection mechanisms are needed within the digital economy ecosystem.